PENINGKATAN AKTIFITAS DAN HASIL BELAJAR MENGGUNAKAN MEDIA KOMIK DAN QUIZ CREATOR PADA PELAJARAN TIK - Arman Arman (PAKAR Pendidikan, 2016)
The study of information technologies have not run optimally because description of the lesson in the form is more theory than practice. From early observations that authors do look a lot of student who are less active during learning and concrentation when seen from the results of daily value activity, many students not get the KKM (Kriteria Ketuntasan Minimum) is 80 score. The problem because teacher who prefer knowledge, put students as objects not as a subject, as well teachers less varying methods used, consequenltly increasing learning motivation of students does not occur. This type of research is a class action research which to improve the learning results of activity and learners by utilizing the medium of comics and quiz creatior on the subjects of information and communication technologies (ICT) in class IX.8 SMP Negeri 7 Padang as well as expected educators can employ the use of comics and quiz creator in ICT learning. The goal of ICT learning achieved and can increase the activity of learners who have an impact on the results of the learning.